George Fort Milton papers - Milton, George Fort, 1894-1955.
Correspondence, memoranda, speeches, writings, research and historical source material, biographical material, scrapbooks, printed matter, photographs, and other papers relating primarily to Milton's career as a historian of the Civil War, newspaper editor, and advisor in the national government. Documents his work as president and editor of the Chattanooga News and editorial writer for the St. Louis Post-Dispatch and the Buffalo Evening News. Also documents his service as member of the Southern Commission on the Study of Lynching in the 1930s; advisor at the Inter-American Conference for the Maintenance of Peace, Buenos Aires, Argentina, in 1936; and special assistant to U.S. Secretary of State Cordell Hull in 1937. Subjects include Stephen A. Douglas, Andrew Johnson, the Tennessee Valley Authority, lynching in the South, and other national and local political issues.
Correspondents include Paul M. Angle, Stringfellow Barr, Francis Biddle, William Jennings Bryan, William Edgar Borah, Henry Steele Commager, E. Merton Coulter, Josephus Daniels, Paul H. Douglas, James A. Farley, Douglas Southall Freeman, Cordell Hull, Marquis James, Estes Kefauver, David Eli Lilienthal, Thomas Powderly Martin, W.G. McAdoo, Kenneth Douglas McKellar, Samuel Davis McReynolds, Allan Nevins, George W. Norris, George Foster Peabody, Arthur Franklin Raper, Franklin D. Roosevelt, Daniel C. Roper, Francis Bowes Sayre, Sumner Welles, William Allen White, and Fort family members.
Library of Congress Motion Picture, Broadcasting, and Recorded Sound Division.
Editor, historian, advisor to diplomatic delegations, consultant to U.S. government agencies, and special assistant to U.S. Secretary of State Cordell Hull.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: Angle, Paul M. -- 1900-1975 -- Correspondence; Barr, Stringfellow, -- 1897-1982 -- Correspondence; Biddle, Francis, -- 1886-1968 -- Correspondence; Borah, William Edgar, -- 1865-1940 -- Correspondence; Bryan, William Jennings, -- 1860-1925 -- Correspondence; Commager, Henry Steele, -- 1902-1998 -- Correspondence; Coulter, E. Merton -- 1890- -- Correspondence; Daniels, Josephus, -- 1862-1948 -- Correspondence; Douglas, Paul H. -- 1892-1976 -- Correspondence; Douglas, Stephen A. -- 1813-1861.; Farley, James A. -- 1888-1976 -- Correspondence; Freeman, Douglas Southall, -- 1886-1953 -- Correspondence; Hull, Cordell, -- 1871-1955.; Hull, Cordell, -- 1871-1955 -- Correspondence; James, Marquis, -- 1891-1955 -- Correspondence; Johnson, Andrew, -- 1808-1875.; Kefauver, Estes, -- 1903-1963 -- Correspondence; Lilienthal, David Eli, -- 1899-1981 -- Correspondence; Martin, Thomas Powderly, -- 1887-1963 -- Correspondence; McAdoo, W. G. -- 1863-1941 -- Correspondence; McKellar, Kenneth Douglas, -- 1869-1957 -- Correspondence; McReynolds, Samuel Davis, -- 1872-1939 -- Correspondence; Nevins, Allan, -- 1890-1971 -- Correspondence; Norris, George W. -- 1861-1944 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Raper, Arthur Franklin, -- 1899-1979 -- Correspondence; Roosevelt, Franklin D. -- 1882-1945 -- Correspondence; Roper, Daniel C. -- 1867-1943 -- Correspondence; Sayre, Francis Bowes, -- 1885-1972 -- Correspondence; Welles, Sumner, -- 1892-1961 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Fort family -- Correspondence; United States. -- Department of State; Southern Commission on the Study of Lynching; Tennessee Valley Authority; Buffalo evening news; Chattanooga news; St. Louis post-dispatch.; African Americans -- Southern States; American newspapers -- Missouri -- Saint Louis; American newspapers -- New York (State) -- Buffalo; American newspapers -- Tennessee -- Chattanooga; Lynching -- Southern States; Pan-Americanism.; Peace -- Congresses; Racism -- Southern States; Latin America -- Foreign relations -- United States; Southern States -- Social conditions; Southern States -- Race relations; Tennessee -- Politics and government -- 1865-1950.; Tennessee River Valley -- History; United States -- Foreign relations -- 20th century; United States -- Foreign relations -- Latin America; United States -- History -- Civil War, 1861-1865.; United States -- Politics and government -- 1901-1953.; Editors; Historians; Public officials